Risk factors for revision surgery following radial head arthroplasty without cement for unreconstructible radial head fractures: Minimum 3-Year Follow-up - Nolte, Philip-Christian; Nolte, Anna-Katharina; Grötzner-Schmidt, Corinna; Jung, Matthias; Porschke, Felix; Grützner, Paul Alfred; Gühring, Thorsten; Schüler, Svenja; Schnetzke, Marc (The journal of bone & joint surgery. A, American volume, 2021)
Background: - Revision rates following radial head arthroplasty (RHA) for unreconstructible radial head fractures (RHFs) differ vastly in the literature, and little is known about the risk factors that are associated with revision surgery. The purposes of this study were to assess the revision rate following RHA and to determine the associated risk factors. - Methods: - A total of 122 patients (mean age, 50.7 years; range, 18 to 79 years) with 123 RHAs who underwent RHA for unreconstructible RHFs between 1994 and 2014 and were ≥3 years out from surgery were included. Demographic variables, injury and procedure-related characteristics, radiographic findings, complications, and revision procedures were assessed. Cox regression analysis was performed to identify the risk factors that were associated with revision surgery following RHA. - Results: - The median follow-up for the study cohort was 7.3 years (interquartile range [IQR], 5.1 to 10.1 years). All of the patients had unreconstructible RHFs: Mason-Johnston type-IV injuries were the most prevalent (80 [65%]). One or more associated osseous or ligamentous injuries were seen in 89 elbows (72.4%). The median time to surgery was 7 days (IQR, 3 to 11 days). Implanted prostheses were categorized as rigidly fixed (65 [52.8%]) or loosely fixed (58 [47.2%]). A total of 28 elbows (22.8%) underwent revision surgery at a median of 1.1 years (IQR, 0.3 to 3.8 years), with the majority of elbows (17 [60.7%]) undergoing revision surgery within the first 2 years. The most common reason for revision surgery was painful implant loosening (14 [29.2% of 48 complications]). Univariate Cox regression suggested that Workers’ Compensation claims (hazard ratio [HR], 5.48; p < 0.001) and the use of an external fixator (HR, 4.67; p = 0.007) were significantly associated with revision surgery. - Conclusions: - Revision rates following RHA for unreconstructible RHFs are high; the most common cause for revision surgery is painful implant loosening. Revision surgeries are predominantly performed within the first 2 years after implantation, and surgeons should be aware that Workers’ Compensation claims and the use of an external fixator in management of the elbow injury are associated with revision surgery. - Level of Evidence: - Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.
Gesehen am 06.09.2021